(untitled) (Reflection and Critique Law Magazine, 2022)
The general objetive of this research is to debate the importance of Constitutional Law in the labor sphere, with regard to the fundamental right to health, inherent to all citizens, and to workers. In addition, the relevance of this theme for constitucionalismo i salso highlighted, in transdisciplinarity and limited effectiveness of some rules of the 1988 Constitution, which delegate the regulation for infraconstitutional rules, such as the Consolidation of Labor Laws (CLT). And the question remains, to what extent do we live a liberalism in which one can “buy” or value the risk to the health or life of a human being? Is it not a form of renounce the constitutional right, fundamental and, therefore, irrevocable?